2003
DOI: 10.1590/s0102-311x2003000100039
|View full text |Cite
|
Sign up to set email alerts
|

Atividade de detergentes e desinfetantes sobre a evolução dos ovos de Ascaris lumbricoides

Abstract: Ascaris lumbricoides infection is acquired via ingestion of embryonated eggs of the parasite, thus justifying the search for ovicidal compounds. We studied the effect of 16 household and laboratory detergents and disinfectants on the embryogenesis of this helminth. Children carrying this infection were treated with levamisole. Eliminated female worms were collected and dissected to obtain eggs from the uteri. The eggs were placed in contact with various products at different dilutions and for various periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…Eggs of A. suum and other ascarids contaminate soil, water and foods (Gupta et al 2009). Once these eggs are present in foods they become extremely difficult to be removed because of their ability to adhere to food surfaces (Massara et al 2003). Thus, the knowledge of the biology of free-living stages of this and other gastrointestinal nematodes can help in developing appropriate control programs.…”
Section: Introductionmentioning
confidence: 99%
“…Eggs of A. suum and other ascarids contaminate soil, water and foods (Gupta et al 2009). Once these eggs are present in foods they become extremely difficult to be removed because of their ability to adhere to food surfaces (Massara et al 2003). Thus, the knowledge of the biology of free-living stages of this and other gastrointestinal nematodes can help in developing appropriate control programs.…”
Section: Introductionmentioning
confidence: 99%
“…Ascaris eggs have great adhesiveness capacity (Massara et al, 2003) because the outermost layer consists of mucopolysaccharides and proteins (Souza et al, 2011). Capizzi & Schwartzbrod (2001) suggested that the surface of Ascaris eggs has hydrophobic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Among the parasites observed in this study, four helminth eggs of the genus Ascaris stand out, one of which was identified as A. lumbricoides. It is known that the eggs of this parasite have a great capacity of adherence to surfaces (27) and, therefore, it is possible to admit the possibility that more eggs, which were not removed during the washing process, could be found in the vegetables.…”
Section: Discussionmentioning
confidence: 99%